Consulting with young people about healthcare. Part I: experience of the hospital environment. Issue 2 (April 2010) - McKenzie, Sian; Norrish, Sara; Parker, Leah; Frampton, Ian
The NHS policy in the UK recommends that the built hospital environment should cater for the needs of younger and older children, adolescents and carers. However, previous studies have indicated that addressing the needs of such a wide age range is a challenge, and that the hospital design and systems are typically more appropriate for children of a younger age rather than adolescents. The aim of the present study was to explore how adolescents, who had not been regular patients, experience the hospital environment and their interactions with staff. Using qualitative methodology, we explore the responses of four young individuals who participated in an innovative filmed hospital intervention study documentary. Results suggest that a pediatric ward designed specifically for adolescents was experienced positively by participants. Other areas of the hospital serving a wide age range of patients (e.g., the emergency and radiography departments) were not experienced as positively. Implications for hospital design, staff training and future research using multimedia approaches are explored.